1989
DOI: 10.1177/002246698902300302
|View full text |Cite
|
Sign up to set email alerts
|

Employment of Youth with and without Handicaps Following High School

Abstract: Factors associated with the employment status of students with and without handicaps were investigated in a sample of 133 youths from nine Vermont school districts. Students with handicaps who exited high school in 1984-85, and who had been receiving special education services, were identified and compared to non-college-bound, vocationally oriented students without handicaps. Two sets of interviews were conducted, one in 1986 and one in 1987. During these interviews, information was obtained on current employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 6 publications
3
24
0
3
Order By: Relevance
“…Between 1995 and 1996 ten students with a mean grade equivalent score of 4.9 (mean raw score 31, mean percentile 17, range 15-43) on the (SDRCT), who were placed in inclusive settings with no LA support, moved or dropped out It is important to note that these students who dropped out are reading disabled as assessed by the SDRCT. Thus these findings on dropout are consistent with the findings of Levin, Zigmond, and Birch (1985), Blackorby, Edgar, andKortering (1991), andHasazi, Johnson, Hasazi, Gordon, andHull (1989) who note that up to 51% of learning disabled are believed to drop out of school without completing grade 12. However, most of the research literature examines the dropout behaviour of grade ten to twelve students; little research examines the dropout process before grade ten and little research examines the connection between school achievement failure, behavioural problems, dropout, and reading failure.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Between 1995 and 1996 ten students with a mean grade equivalent score of 4.9 (mean raw score 31, mean percentile 17, range 15-43) on the (SDRCT), who were placed in inclusive settings with no LA support, moved or dropped out It is important to note that these students who dropped out are reading disabled as assessed by the SDRCT. Thus these findings on dropout are consistent with the findings of Levin, Zigmond, and Birch (1985), Blackorby, Edgar, andKortering (1991), andHasazi, Johnson, Hasazi, Gordon, andHull (1989) who note that up to 51% of learning disabled are believed to drop out of school without completing grade 12. However, most of the research literature examines the dropout behaviour of grade ten to twelve students; little research examines the dropout process before grade ten and little research examines the connection between school achievement failure, behavioural problems, dropout, and reading failure.…”
Section: Discussionsupporting
confidence: 88%
“…There may be more students with leaming disabilities who have not been labelled as such. To further support these data, Hasazi, Johnson, Hasazi, Gordon, and Hull ( 1989), in a longitudinal study of Vermont students, found that 36% of students with handicaps left or dropped out of school before graduation. In addition, 13% of the students with handicaps left school at ages 15-16 and 20% exited between ages 20-22.…”
Section: Dropout Ratesmentioning
confidence: 95%
See 2 more Smart Citations
“…Doren and Benz (2001) reviewed studies published between 1972 and 1998 that addressed gender, disability, and transition outcomes and found that women with disabilities were more likely to be unemployed, had significantly lower wages, were more likely to have unskilled jobs (e.g., litde ot no opportunity for advancement), and experienced less job stability than men with disabilities. Hasazi and her colleagues also summarized research investigating the transition outcomes of youth with disabilities and fouhd similar trends; after exiting high school, young women with disabilities were more likely than young men with disabilities to be unemployed, underemployed, or employed in low status jobs (Hasazi, Johnson, Hasazi, Gordon, & Hull, 1989). More recently, and Best (2006) used the National Education Longitudinal Study of 1988 data set to examine the extent to which outcome variables were differentially associated with gender for students patticipating in special education.…”
mentioning
confidence: 94%